Mobile Broadband Internet, Poverty and Labor Outcomes in Tanzania - Bahia, Kalvin; Castells, Pau; Cruz, Genaro; Masaki, Takaaki; Rodriguez-Castelan, Carlos; Sanfelice, Viviane (World Bank, Washington, DC, 2021)
What are the impacts of expanding mobile broadband coverage on poverty, household consumption and labor market outcomes in developing countries? Who benefits from improved coverage of mobile internet? To respond to these questions, this paper applies a difference-in-differences estimation using panel household survey data combined with geospatial information on the rollout of mobile broadband coverage in Tanzania. The results reveal that being covered by 3G networks has a large positive effect on total household consumption and poverty reduction, driven by positive impacts on labor market outcomes. Working age individuals living in areas covered by mobile internet witnessed an increase in labor force participation, wage employment, and non-farm self-employment, and a decline in farm employment. These effects vary by age, gender and skill level. Younger and more skilled men benefit the most through higher labor force participation and wage employment, while high-skilled women benefit from transitions from self-employed farm work into non-farm employment.